Penerapan Akuntansi Pertanggungjawaban sebagai Alat Pengendalian Biaya Produksi dan Penilaian Kinerja pada UPT. Sikka Innovation Centre - Ermiana Riyanti; Henrikus Herdi; Siktania Maria Dilliana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Research This study aims to determine the application of accountability accounting as a tool for production cost control and performance appraisal at UPT. production cost control and performance appraisal at Sikka Innovation Center. innovation center. In the application of responsibility accounting there are several indicators, namely, organizational structure, budget, separation of controllable and uncontrollable costs, account code classification, account reporting, and performance appraisal at UPT. controlled and uncontrolled, account code classification, accountability report. accountability report. Implementation of accountability accounting as a performance appraisal tool There are several indicators, namely, identification of the center of responsibility center, standards are set as benchmarks for manager performance on certain responsibility center, manager performance is measured by comparing the budget and realization between budget and realization, managers are individually rewarded or punished by higher management. or punishment from higher management. This research uses a qualitative descriptive method. Techniques data collection techniques using literature study, observation, interviews, and documentation. documentation. The data analysis technique is done by comparing the existing theories that already exist with the data obtained from the case study. The research results obtained from the application of accountability accounting as a means of controlling production costs and performance appraisal has not been effective because the and performance appraisal has not been effective because there is no separation between controlled and uncontrolled costs. controlled and uncontrolled costs.